Infantile Iatrogenic Cushing Syndrome due to Topical Steroids - Lulwah Alkhuder; Horia Mawlawi (Hindawi Limited, 2019)
Cushing syndrome is an endocrinological disorder characterized by increased free plasma glucocorticoids level. It is either due to an excessive endogenous release of steroids (e.g., pituitary adenoma or adrenal hyperplasia) or exogenous administration of steroids. In children, iatrogenic Cushing syndrome is the most common form of Cushing syndrome occurring in this age group. The vast majority of cases are due to oral or parenteral preparation of steroids, which are commonly prescribed for pulmonary, hematological, renal, or autoimmune pathologies. Topical preparations can rarely cause Cushing syndrome in young children, and only a few cases were reported in the literature, where the patients were older than 5 months of age. In this report, we present a three-month-old girl who developed iatrogenic Cushing syndrome due to prolonged and inappropriate use of topical clobetasol cream for napkin dermatitis.